Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

High incidence of estrous cycle irregularities in heterogeneous stock (HS) rats is associated with footshock-resistant cocaine intake - Elizabeth A. Sneddon; Supakorn Chonwattanagul; Kathleen Bai; Pranav H. Kurup; Sonja L. Plasil; Michelle R. Doyle; Sélène Zahedi; Sierra Simpson; Benjamin C. Sichel; Dyar N. Othman; Molly Brennan; Abraham A. Palmer; et al. (Psychopharmacology, 2026)
Rationale Hormonal fluctuations throughout the estrous cycle are hypothesized to influence drug-related behaviors. Preclinical models show that some cocaine-related behaviors are influenced by the estrous cycle. However, the extent to which the estrous cycle modulates cocaine self-administration in outbred heterogeneous stock (HS) rats is unknown. Objectives We aimed to examine the relationship between estrous phases and cocaine self-administration behavior in HS rats using an operant model of extended access to cocaine self-administration. Methods We assessed the escalation of intake, breaking point, and resistance to foot shock. Using vaginal swabbing and lavage techniques, we characterized the relationship between estrous phase and cocaine behaviors. We then comprehensively evaluated estrous cycling patterns in young adult and adult HS rats, comparing them with Wistar rats. Results Estrous phase showed no association with cocaine self-administration in HS rats. 82% of female HS rats exhibited irregular estrous cycling with variability to the phase length, even in the absence of drug exposure, a phenomenon not observed in the Wistar strain. Females with irregular cycling showed greater footshock-resistant cocaine intake. Conclusions This study provides the first evidence that most female HS rats exhibit irregular estrous cycling. In HS rats, the estrous phase per se has no major influence on cocaine self-administration, whereas cycling irregularity was associated with specific addiction-related behaviors, including footshock-resistant intake. As HS rats gain popularity in behavioral and genome-wide studies, understanding these cycle disruptions is crucial as they may reveal genetic links into cycling variability and individual differences to aspects of cocaine use.

Individual differences in sick face sensitivity: females are more sensitive to lassitude facial expressions than males - Tiffany S. Leung; Elizabeth A. Simpson (Evolution and Human Behavior, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Otolith-based age and growth of the spotted moray eel (Gymnothorax moringa) and squirrelfish (Holocentrus adscensionis) from Ascension Island and St Helena - Valerio Visconti; Elizabeth D. L. Trip; Ian Woodgate; Tiffany Simpson; James B. Bell; Paul Whomersley; Leeann Henry; Kirsty Jones; Kyne Krusic-Golub; Simon Robertson; Serena Wright (Frontiers in Marine Science, 2025)
This study investigates the age-based life-history traits of two groundfish species, the spotted moray eel ( Gymnothorax moringa ) and squirrelfish ( Holocentrus adscensionis ), found in Ascension Island and St Helena. Both islands are part of the UK Overseas Territories (UKOTs) and are known for their fish biodiversity. The research aims to provide essential life-history information to support sustainable management of these species within the Marine Protected Areas (MPAs) of Ascension Island and St Helena. A total of 556 fish samples were collected between 2014 and 2021, with 279 individuals of G. moringa and 277 individuals of H. adscensionis . We found significant differences in life span, adult body size, and growth rates between the two islands for both species. G. moringa exhibited longer life spans (32 vs 29 years) and faster growth rates at Ascension Island compared to St Helena, while H. adscensionis showed larger adult sizes at Ascension Island but shorter life spans (21 vs 27 years) compared to St Helena. The study highlights the importance of developing locality-specific species life history data collections to monitor population dynamics in MPA areas. This biological information is essential to allow future assessment programs on the potential impacts of climate change and inshore human activities, including the impacts of inshore fisheries. Future research should focus on reproductive biology, size and age at maturity, and migration patterns to enhance the accuracy of sustainability assessments for these fisheries.

Assessing behavioural economic demand for morphine after an acute dose in individuals with- and without childhood trauma: a double-blind, randomised, controlled trial - Martin Trøstheim; Benjamin L. Berey; Elizabeth R. Aston; Matthew J. Gullo; Lee Hogarth; Graham Simpson; Rupert Broomby; Celia J. Morgan; Molly Carlyle (Psychopharmacology, 2025)
Background Childhood trauma is associated with positive subjective responses to acute opioids in the laboratory. Yet, its impact on behavioural economic demand for opioids remains unclear. Because demand can predict future use and misuse, we investigated whether individuals with childhood trauma also display greater demand for opioids in the laboratory. Methods This secondary analysis used data from a double-blind, randomised, controlled, counterbalanced trial. Across two sessions, individuals with ( n = 26) and without ( n = 21) childhood trauma received a high (0.15 mg/kg) and low (0.01 mg/kg) dose of intramuscular morphine 120 min before a hypothetical purchase task. Participants also regularly reported their subjective desire for the study drug. Area under the consumption and expenditure curves, and specific demand indices ( O max , P max , breakpoint , intensity , elasticity ), were analysed with non-parametric mixed models. Results Consumption and expenditure for low dose morphine was lower in the childhood trauma group when compared to high dose morphine in this group, and low dose morphine in the control group ( p s ≤ 0.03). Consistent results were obtained for specific demand indices O max , P max , and breakpoint , but not intensity or elasticity . Positive correlations between subjective desire and consumption and expenditure were only observed in the childhood trauma group ( Tau-c = 0.24–0.34, p s ≤ 0.03). Conclusion Under laboratory conditions, desires to use opioids among individuals with childhood traumas may not manifest in strong intentions to acquire these drugs. Diverging results from psychometric measures of subjective and economic opioid value highlight the need for future research to explore contextual and resilience factors to understand how problematic opioid use emerges after childhood traumas.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Multi-centre normative brain mapping of intracranial EEG lifespan patterns in the human brain - Heather Woodhouse; Gerard Hall; Callum Simpson; Csaba Kozma; Frances Turner; Gabrielle M. Schroeder; Beate Diehl; John S. Duncan; Jiajie Mo; Kai Zhang; Aswin Chari; Martin Tisdall; et al. (Brain Structure and Function, 2025)
Understanding healthy human brain function is crucial to identify and map pathological tissue within it. Whilst previous studies have mapped intracranial EEG (icEEG) from non-epileptogenic brain regions, they often neglect age and sex effects. Further, they are limited by small sample sizes due to the modality’s invasive nature. This study substantially expands the subject pool compared to existing literature, to create a multi-centre, normative map of brain activity which considers the effects of age, sex and recording hospital. Using interictal icEEG recordings from $$n = 502$$ subjects across 15 centres, we constructed a normative map of non-pathological brain activity by regressing age and sex on relative band power in five frequency bands. A linear mixed model was implemented to account for the hospital effect. Variable importance was assessed using standard statistical measures, and regression coefficients (and their standard errors) were analysed at both whole-brain and regional scales. Recording hospital significantly impacted normative icEEG maps in all frequency bands, and age was a more influential predictor of band power than sex. The age effect varied by frequency band, but no spatial patterns were observed at the region-specific level. Certainty about regression coefficients was also frequency band specific and moderately impacted by sample size. The concept of a normative map is well-established in neuroscience research and particularly relevant to the icEEG modality, which does not allow healthy control baselines. Our key results regarding the hospital site and age effect guide future work utilising normative maps in icEEG.

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

Ice-marginal volcanic sequence in Iceland found on a nondescript gradual hillslope: An unexpected record of ice thickness late in deglaciation - Audrey R. Putnam; Kirsten L. Siebach; Candice C. Bedford; Sarah L. Simpson; Michael T. Thorpe; Joseph J. Tamborski; Elizabeth B. Rampe (Journal of Volcanology and Geothermal Research, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Testing in-situ apatite Lu–Hf dating in polymetamorphic mafic rocks: a case study from Palaeoproterozoic southern Australia - Dillon A. Brown; Anthony Reid; Elizabeth A. Jagodzinski; Megan Williams; Alex Simpson; Mark Pawley; Christopher L. Kirkland; Claire Wade; Alexander T. De Vries Van Leeuwen; Stijn Glorie (Contributions to Mineralogy and Petrology, 2024)
In mafic systems where primary mineral assemblages have witnessed moderate- to high-temperature hydrous overprinting and deformation, little is known about the retentivity of the Lu–Hf isotopic system in apatite. This study presents apatite laser-ablation Lu–Hf and U–Pb geochronology, zircon geochronology, and detailed petrological information from polymetamorphic mafic intrusions located in the central-western Gawler Craton in southern Australia, which records an extensive tectonometamorphic history spanning the Neoarchaean to the Mesoproterozoic. Zircon records magmatic crystallisation ages of c. 2479–2467 Ma, coinciding with the onset of the c. 2475–2410 Ma granulite-facies Sleafordian Orogeny. The amphibole-dominant hydrous assemblages which extensively overprint the primary magmatic assemblages are hypothesised to post-date the Sleafordian Orogeny. The Lu–Hf and U–Pb isotopic systems in apatite are used to test this hypothesis, with both isotopic systems recording significantly younger ages correlating with the c. 1730–1690 Ma Kimban Orogeny and the c. 1590–1575 Ma Hiltaba magmatic event, respectively. While the early Mesoproterozoic apatite U–Pb ages are attributed to thermal re-equilibration, the older Lu–Hf ages are interpreted to reflect re-equilibration facilitated primarily by dissolution-reprecipitation, but also thermally activated volume diffusion. The mechanisms of Lu–Hf isotopic resetting are distinguished based on microscale textures and trace element abundances in apatite and the integration of apatite-amphibole textural relationships and temperatures determined from the Ti content in amphibole. More broadly, the results indicate that at low to moderate temperatures, apatite hosted in mafic rocks is susceptible to complete recrystallisation in rocks that have weak to moderate foliations. In contrast, at higher temperatures in the absence of strain, the Lu–Hf system in apatite is comparatively robust. Ultimately, the findings from this study advance our understanding of the complex role that both metamorphism and deformation play on the ability of mafic-hosted apatite to retain primary Lu–Hf isotopic signatures.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Improving the representation of groundwater processes in a large-scale water resources model - Helen Elizabeth Baron; Virginie D. J. Keller; R. Horan; Donald John MacAllister; Mike Simpson; Christopher R. Jackson; Helen A. Houghton-Carr; Nathan Rickards; Kaushal K. Garg; Muddu Sekhar; Alan MacDonald; Gwyn Rees (Hydrological Sciences Journal, 2023)

The role of acoustics within the sensory landscape of coral larval settlement - Josh W. Pysanczyn; Elizabeth A. Williams; Emelie Brodrick; Daniel Robert; Jamie Craggs; Kristen L. Marhaver; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Recruitment of coral larvae on reefs is crucial for individual survival and ecosystem integrity alike. Coral larvae can detect and respond to a wide range of biotic and abiotic cues, including acoustic cues, to locate suitable sites for settlement and metamorphosis. However, the acoustic ecology of coral larvae, including how they perceive auditory cues, remains poorly understood. In this mini-review we consider both ex situ physiology and behavior, and in situ ecological and behavioral studies, to first provide an updated overview of the abiotic and biotic cues used by coral larvae to guide settlement. We then explore in detail the use of acoustic cues and the current literature on behavioral responses to acoustic stimuli. Finally, we discuss gaps in our understanding of the mechanisms by which coral larvae detect acoustic cues, highlighting a novel application of technology to explore these sensory capabilities. We also address how larval phonotaxis, i.e., the ability to orient to a sound cue, can be applied to coral reef conservation. Current research suggests that acoustic cues are likely used at small spatial scales, and that coral larvae may have directional acoustic sensitivity enabling phonotactic behavior. Recruitment of coral larvae on reefs is significantly influenced by habitat-specific soundscape variation and likely affected by anthropogenic disturbance. We propose a novel application of the remote sensing technology, micro-scanning laser Doppler vibrometry (LDV), to quantify the micromechanical responses of putative acoustically sensitive epidermal microstructures. We then highlight the potential for incorporation of acoustic enrichment techniques in coral reef conservation and restoration interventions.

Usability of existing global and national data for flood related vulnerability assessment in Indonesia - Breanne K. Langlois; Elizabeth Marsh; Tyler Stotland; Ryan B. Simpson; Katherine Berry; David A. Carroll; Aris Ismanto; Magaly Koch; Elena N. Naumova (Science of The Total Environment, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Design of a Drug-Eluting Subcutaneous Implant of the Antiretroviral Tenofovir Alafenamide Fumarate - Solange M Simpson; Lakmini Widanapathirana; Jonathan T. Su; Samuel Sung; David Watrous; Jiang Qiu; Elizabeth Pearson; Alex Evanoff; Dipu Karunakaran; Jorge E. Chacon; Patrick F. Kiser (Pharmaceutical Research, 2020)
Purpose Sexual transmission of HIV has been clinically proven to be preventable with a once-daily oral tablet; however, missed doses dramatically increase the risk of HIV infection. Long-acting subcutaneous implants do not allow the user to miss a dose. A desirable long-acting drug-eluting implant can deliver a constant amount of drug, adjust the delivered dose, and be readily manufactured. We present a long-acting, subcutaneous implant design composed of tenofovir alafenamide hemifumarate (TAF) pellets loaded in a sealed polyether urethane tube for the prevention of HIV transmission. Methods Implants were prepared with pressed drug pellets and extruded polyurethane tubing. In vitro release rate of implants using different pellet formulations, rate-controlling membranes, and geometries were measured. Results Tenofovir alafenamide release appeared to be governed by a pseudo-steady state and followed a mass transport model of release from a cylindrical drug reservoir. Implant seal integrity was tested and confirmed using mechanical testing. The inclusion of sodium chloride in the pellet increased the release rate and reduced initial lag. The release was sustained for 100 days. Conclusions The release rate of tenofovir alafenamide mechanistically varied with geometry and rate controlling membrane composition. The polyether urethane implant presented herein is modular and tunable to adjust the release rate and duration of the TAF release.

Ozone pollution will compromise efforts to increase global wheat production - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Malin Broberg; Johan Uddling; Fernando Jaramillo; William J Davies; Frank Dentener; Maurits Van den Berg; Madhoolika Agrawal; Shahibhushan B. Agrawal; et al. (Global Change Biology, 2018)
Introduction of high‐performing crop cultivars and crop/soil water management practices that increase the stomatal uptake of carbon dioxide and photosynthesis will be instrumental in realizing the United Nations Sustainable Development Goal ( SDG ) of achieving food security. To date, however, global assessments of how to increase crop yield have failed to consider the negative effects of tropospheric ozone, a gaseous pollutant that enters the leaf stomatal pores of plants along with carbon dioxide, and is increasing in concentration globally, particularly in rapidly developing countries. Earlier studies have simply estimated that the largest effects are in the areas with the highest ozone concentrations. Using a modelling method that accounts for the effects of soil moisture deficit and meteorological factors on the stomatal uptake of ozone, we show for the first time that ozone impacts on wheat yield are particularly large in humid rain‐fed and irrigated areas of major wheat‐producing countries (e.g. United States, France, India, China and Russia). Averaged over 2010–2012, we estimate that ozone reduces wheat yields by a mean 9.9% in the northern hemisphere and 6.2% in the southern hemisphere, corresponding to some 85 Tg (million tonnes) of lost grain. Total production losses in developing countries receiving Official Development Assistance are 50% higher than those in developed countries, potentially reducing the possibility of achieving UN SDG 2. Crucially, our analysis shows that ozone could reduce the potential yield benefits of increasing irrigation usage in response to climate change because added irrigation increases the uptake and subsequent negative effects of the pollutant. We show that mitigation of air pollution in a changing climate could play a vital role in achieving the above‐mentioned UN SDG , while also contributing to other SDG s related to human health and well‐being, ecosystems and climate change.

Effects of sprint interval training on ectopic lipids and tissue-specific insulin sensitivity in men with non-alcoholic fatty liver disease - Jack A. Sargeant; Stephen Bawden; Guruprasad P. Aithal; Elizabeth J. Simpson; Ian A. Macdonald; Mark C. Turner; Jessica Cegielski; Kenneth Smith; James L. Dorling; Penny A. Gowland; Myra A. Nimmo; James A. King (European Journal of Applied Physiology, 2018)

Acute oxytocin improves memory and gaze following in male but not female nursery-reared infant macaques - Elizabeth A. Simpson; Annika Paukner; Valentina Sclafani; Stefano S. K. Kaburu; Stephen J. Suomi; Pier F. Ferrari (Psychopharmacology, 2017)

Non-consumptive Effects of Native Deer on Introduced Earthworm Abundance - Andrea Dávalos; Elizabeth Simpson; Victoria Nuzzo; Bernd Blossey (Ecosystems, 2015)

Separate and combined effects of 21-day bed rest and hypoxic confinement on body composition - Tadej Debevec; Tarsi C. Bali; Elizabeth J. Simpson; Ian A. Macdonald; Ola Eiken; Igor B. Mekjavic (European Journal of Applied Physiology, 2014)

Parental occupational paint exposure and risk of childhood leukemia in the offspring: findings from the Childhood Leukemia International Consortium - Helen D. Bailey; Lin Fritschi; Catherine Metayer; Claire Infante-Rivard; Corrado Magnani; Eleni Petridou; Eve Roman; Logan G. Spector; Peter Kaatsch; Jacqueline Clavel; Elizabeth Milne; John D. Dockerty; et al. (Cancer Causes & Control, 2014)

Erratum to: Beyond knockouts: cre resources for conditional mutagenesis - Stephen A. Murray; Janan T. Eppig; Damian Smedley; Elizabeth M. Simpson; Nadia Rosenthal (Mammalian Genome, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Beyond knockouts: cre resources for conditional mutagenesis - Stephen A. Murray; Janan T. Eppig; Damian Smedley; Elizabeth M. Simpson; Nadia Rosenthal (Mammalian Genome, 2012)

Laboratory Animal Management Assistant (LAMA): a LIMS for active research colonies - Marko Milisavljevic; Taryn Hearty; Tony Y. T. Wong; Elodie Portales-Casamar; Elizabeth M. Simpson; Wyeth W. Wasserman (Mammalian Genome, 2010)

Adiaspiromycosis Due to Emmonsia crescens is Widespread in Native British Mammals - Andrew M. Borman; Vic R. Simpson; Michael D. Palmer; Christopher J. Linton; Elizabeth M. Johnson (Mycopathologia, 2009)

Essential elements of online information networks on invasive alien species - Annie Simpson; Elizabeth Sellers; Andrea Grosse; Yan Xie (Biological Invasions, 2006)

Transplant tolerance: models, concepts and facts - Nicola J. Monk; Roseanna E. G. Hargreaves; Elizabeth Simpson; Julian P. Dyson; Stipo Jurcevic (Journal of Molecular Medicine, 2006)

Ultraviolet Radiation at Places of Residence and the Development of Melanocytic Nevi in Children (Australia) - Dallas R. English; Elizabeth Milne; Julie A. Simpson (Cancer Causes & Control, 2006)

Nectin-1/HveC Mediates herpes simplex virus type-1 entry into primary human sensory neurons and fibroblasts - Scott A Simpson; Michael D Manchak; Elizabeth J Hager; Claude Krummenacher; J Charles Whitbeck; Myron J Levin; Curt R Freed; Christine L Wilcox; Gary H Cohen; Roselyn J Eisenberg; Lewis I. Pizer (Journal of NeuroVirology, 2005)

“A Japanese gentleman of the Samurai tradition”: Takeshi Matsunaga 1945–2003 - Francesco Colucci; Elizabeth Simpson; Anne McLaren; Satoshi Hayakawa; Elisabet Andersson; Lucia Mincheva-Nilsson; Vladimir Baranov (Immunogenetics, 2003)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Transgenic mice for the preparation of puromycin-resistant primary embryonic fibroblast feeder layers for embryonic stem cell selection - Elizabeth R. Linnell; Charles P. Lerner; Kevin A. Johnson; Craig A. Leach; Thomas R. Ulrich; William C. Rafferty; Elizabeth M. Simpson (Mammalian Genome, 2001)

Revised nomenclature for strain 129 mice - Michael F.W. Festing; Elizabeth M. Simpson; Muriel T. Davisson; Larry E. Mobraaten (Mammalian Genome, 1999)

An expanded collection of mouse Y Chromosome RDA clones - David E. Bergstrom; Hailing Yan; Manjula M. Sonti; Sandya Narayanswami; Janet K. Bayleran; Elizabeth M. Simpson (Mammalian Genome, 1997)